Synthesis of Highly Sulfonated Poly(arylene ether) Containing Multiphenyl for Proton Exchange Membrane Materials - Yi-Chiang Huang; Ruei-Hong Tai; Hsu-Feng Lee; Po-Hsun Wang; Ram Gopal; Chun-Che Lee; Mei-Ying Chang; Wen-Yao Huang (International Journal of Polymer Science)
A series of sterically hindered, sulfonated, poly(arylene ether) polymers were synthesized by nucleophilic polycondensation reaction using 4,4′′′′-difluoro-3,3′′′′-bistrifluoromethyl-2′′,3′′,5′′,6′′-tetraphenyl-[1,1′;4′,1′′;4′′,1′′′;4′′′,1′′′′]-pentaphenyl and 4,4′-biphenol and were prepared through postpolymerization sulfonation. The chemical structures were confirmed by 1H NMR. Subsequent to sulfonation, solvent-casting membranes were provided ion exchange capacity (IEC) values ranging from 0.39 to 2.90 mmol/g. Proton conductivities of membranes ranged from 143 to 228 mS/cm at 80°C under fully humidified conditions which were higher than that of Nafion 117. The membrane also exhibited considerably dimension stability, oxidative stability, and hydrolytic stability. The microphase structure was investigated by transmission electron microscopy (TEM) and the ionic aggregation of sulfonic acid groups exhibited spherical ionic clusters with well-developed phase separated morphology. The results indicated that the membranes are promising candidates for application as proton exchange membranes. This investigation demonstrates introducing multiphenylated moieties to create a high free volume polymer that provides dimensionally stable and high proton conductivity membranes.